Thermodynamics of the complexation of curium(III) with chloride in alkali and alkali earth metal solutions at elevated temperatures - Koke, Carsten; Skerencak-Frech, Andrej; Panak, Petra (The journal of chemical thermodynamics, 2019)
The complexation of trivalent curium (Cm(III)) with chloride up to its respective saturation concentration is studied in dependency of the chloride-bearing electrolyte (LiCl, NaCl, MgCl2, CaCl2) in the temperature range of 25-200°C by time-resolved laser fluorescence spectroscopy (TRLFS). At low chloride concentrations and temperatures the Cm(III) aquo ion dominates the species distribution. However, at both elevated chloride concentrations and temperatures speciation is dominated by CmCl2+(aq) and CmCl2+(aq), and significant molar fractions are even contributed by CmCl3 (aq) and CmCl4-(aq). Conditional stability constants log β′n(t) are determined and extrapolated to the thermodynamic reference state using the specific ion-interaction theory (SIT). Modeling results in standard stability constants log β°2(t) with slight deviation with respect to the valency of the electrolyte. As a result, an average value of log β°2(25°C)=(−1.16±0.10) is derived for the formation of CmCl2+. The complexation is found to be both endothermic as well as entropy driven with ΔrH°=(60.5±1.5) kJmol−1, and ΔrS°=(180.7±3.9) Jmol−1K−1.